Anthracyclines in Early Breast Cancer: The ABC Trials-USOR 06-090, NSABP B-46-I/USOR 07132, and NSABP B-49 (NRG Oncology) - Blum, JL (2017)
Purpose Docetaxel and cyclophosphamide (TC) was superior to doxorubicin and cyclophosphamide (AC) in a trial in early breast cancer. However, activity of TC relative to AC regimens with a taxane (TaxAC) is unknown. Methods In a series of three adjuvant trials, women were randomly assigned to TC for six cycles (TC6) or to a standard TaxAC regimen. US Oncology Research (USOR) 06-090 compared TC6 with docetaxel, doxorubicin, and cyclophosphamide (TAC6). National Surgical Adjuvant Breast and Bowel Project (NSABP) B-46-I/USOR 07132 compared TC6, TAC6, or TC6 plus bevacizumab. NSABP B-49 compared TC6 with several standard AC and taxane combination regimens. Before any analysis of individual trials, a joint efficacy analysis of TC versus the TaxAC regimens was planned, with invasive disease-free survival (IDFS) as the primary end point. Patients who received TC6 plus bevacizumab on NSABP B-46-I/USOR 07132 were not included. A hazard ratio (HR) from a stratified Cox model that exceeded 1.18 for TC6 versus TaxAC was predefined as inferiority for TC6. The prespecified interim monitoring plan was to report for futility if the HR was > 1.18 when 334 IDFS events were observed (50% of 668 events required for definitive analysis). Results A total of 2,125 patients were randomly assigned to receive TC6 regimens and 2,117 patients were randomly assigned to receive TaxAC regimens. The median follow-up time was 3.3 years. There were 334 IDFS events, and the HR for TC6 versus TaxAC was 1.202 (95% CI, 0.97 to 1.49), which triggered early reporting for futility. The 4-year IDFS was 88.2% for TC6 and was 90.7% for TaxAC ( P = .04). Tests for treatment interaction by protocol, hormone receptor status, and nodal status were negative. Conclusion The TaxAC regimens improved IDFS in patients with high-risk human epidermal growth factor receptor 2-negative breast cancer compared with the TC6 regimen.